An optimality theoretic-based analysis of consonant cluster pronunciation errors among Iraqi EFL learners - Zohreh Sadat Naseri; fatemeh Ahmadinasab; Rawaa Kadhem Jawaad (زبان پژوهی)
This study examines the pronunciation errors of English consonant clusters among Iraqi EFL learners through the lens of Optimality Theory (OT).  For this aim, 40 first-year university students of different majors aged 18-25 years were selected from beginner and lower-intermediate levels based on their scores on Oxford Placement Test. Using different instruments, such as reading instruction and read-aloud test, and being informed from the category of major pronunciation problems by Arabic learners presented by Yavaş (2011), an Optimality Theory-based analysis was adopted in the research. Findings indicated that in pronouncing initial clusters of two consonants, *COMPLEX onset as the high-ranked constraint is frequently violated in Iraqi Arabic (IA), because in IA there are many words started with #CCV. Also, *#CCC is never violated in IA. Since constraints are universal, languages differ only in how they rank them. In pronouncing a coda cluster consisting of two consonants, although *CCcoda is never violated in IA, this constraint is not permuted in the pronunciation of the participants. However, to pronounce words with the structure of VCCC(C)#, it seems that the two low-ranked constraints, namely *CCCCcoda and *CCCcoda in English are permuted to high-ranked constraints in the pronunciation of IA learners.